Everyday life in a prison : confinement, surveillance, resistance - Mahuya Bandyopadhyay (New Delhi : Orient BlackSwan, 2010)
Based on the fieldwork in a Alipore Jail, a central prison in Kolkata, India.
Keywords: Prisoners India; Penal Institution Social Aspects; Imprisonment Detension; Prison Ethanography; Social Sciences